Implementasi Hukum Waris Islam Di Rukun Kematian Ad Da’wah Lr. Kampung Jawa Tembilahan Kota - Munawarah, St. Rukmana Ratu; Herdiansyah; Rahmiati; Saputri, Yesi Kasma; Tendriandi, Rudi; Muda, Sultan Iskandar; Juari, Iskandar (Indra Institute Research & Publication, 2024)
Islamic law covers all aspects of human life, both in this world and in the hereafter. As is well known, the rules of Allah in the form of Islamic law have been categorized by experts into two major groups. First, the law of 'ibadah, which is a rule concerning the relationship between man and his creator (Hablumminallah). Second, the law of mu'amalat, which concerns the legal system of relations between fellow humans and the surrounding nature (Hablumminannas). Among the laws governing human relations with others that have been determined by Allah is one of them inheritance. Before the distribution of inheritance property, the family must carry out obligations including organizing the corpse, paying off debts and wills. For this reason, the Ad-Da’wah death pillar was formed to make it easier for families to fulfill their obligations in organizing the corpse. The Ad-Da’wah death association was formed in 2016 and until now the Ad-Da’wah death association is still running with 300 members. The law of inheritance must be distributed to the heirs if the property owned is still remaining. The division of inheritance is divided into three ways, the first is the division of inheritance according to Islam, the division of inheritance based on customary law and based on western law or the Civil Code. As a Muslim, we should use Islamic inheritance law in the distribution of inheritance as stated in the Qur'an.